Ultraslow Spreading Processes - A Microseismicity Study of the Knipovich Ridge - Meier, Michaela (Universität Bremen, 2022)
Along the global mid-ocean ridge system, new seafloor is constantly formed as tectonic plates drift apart. When spreading rate is reduced to less than 20 mm/yr the spreading dynamics change drastically and thereby the entire appearance of these ultraslow spreading ridges differs from faster spreading ridges. Melt is unevenly distributed such that volcanic centers receive more melt than the ridge on average does. Amagmatic segments in between are the melt-poor counterpart. The process of melt focusing is suggested to guide melt along the lithosphere – asthenosphere boundary from amagmatic segments towards volcanic centers. Until now, the processes acting at ultraslow spreading ridges are not completely understood. Key questions are the scale of melt focusing and how melt is extracted at the volcanic centers, the role of detachment faults and the extent of rock alteration. With a microseismicity study on the scale of an entire segment, spanning from one volcanic center to another, these questions could be addressed. The unique microseismicity study was conducted at the Knipovich Ridge, that is a very oblique, ultraslow spreading ridge and part of the Arctic Ridge System. The ocean bottom seismometer network of in total 30 stations was deployed for around one year along 160 km of the rift axis. It covered the Logachev volcanic center, which is the major volcanic center of the Knipovich Ridge, and a second volcanic center south of it. For the recorded data I used automatic earthquake detection and picking of P- and S-phases with a subsequent manual pick check. In this way I extracted in total 14401 earthquakes from the recorded data in the study area. The earthquakes in this comprehensive earthquake catalog were located with different algorithms. 8435 earthquakes with a maximum depth error and Smajor of 5 km and a RMS of 0.4 s were classified as reliably located and used for further interpretations. I determined fault plane solutions for 44 events. Furthermore, I used the earthquakes for a local earthquake ...